(untitled) (SAARC Journal of Agriculture, 2017)
In order to study the influence of weather factors on the abundance and population dynamics of Spodoptera litura F. and Pieris brassicae L. on cabbage, a field experiment was conducted. Larval population of S. litura ranged from 0.56 to 1.57 larvae/plant during 8 January to 12 February 2014 crop season while the highest peak was on 5 February 2014 (1.57 larvae/plant) at 29.5 0C temperature. In case of Pieris brassicae, larval population ranged from 0.58 to1.98 larvae/plant and the highest peak of P. brassicae was also on 5 February. The highest peak was on 5 February 2014 at 96% and 38% relative humidity of both maximum and minimum categories and the highest peak of P. brassicae was on 5 February. There was a strong positive correlation (r = 0.824 and r = 0.920) between population of Spodoptera litura and temperature (maximum and minimum). On the other hand, there was a negative correlation (r = -0.439) between population of S. litura and maximum relative humidity and a strong negative correlation (r = - 0.716) between population of S. litura and minimum relative humidity. The population of Pieris brassicae was positively correlated (r = 0.899 and r = 0.956) with maximum and minimum temperatures. There was a negative correlation (r = -0.443) between population of P. brassicae and maximum relative humidity and a strong negative correlation (r = - 0.645) between population of P. brassicae and minimum relative humidity. SAARC J. Agri., 15(1): 13-21 (2017)